Joint Gain/Phase and Mutual Coupling Array Calibration Technique with Single Calibrating Source - Wei Chen; Joni Polili Lie; Boon Poh Ng; Tao Wang; Meng Hwa Er (International Journal of Antennas and Propagation)
An iterative-based method for joint gain/phase and mutual coupling array calibration is proposed in this paper. It estimates the array gain/phase and mutual coupling coefficients with a set of simultaneous equations formed by using the beam pattern property of the array. Only one calibrating source with known direction is requiblue to obtain the unique estimate. The effectiveness of this approach is illustrated by simulation results and by experimental data collected with an antenna array operating in high-frequency radio band.